Molecular authentication and phytochemical assessment of Ruscus hyrcanus Woron. (Asparagaceae) based on trnH- psbA barcoding and HPLC-PDA analysis. (May 2020) - Ghorbani, Salimeh; Sonboli, Ali; Ebrahimi, Samad Nejad; Mirjalili, Mohammad Hossein
Abstract: Ruscus hyrcanus Woron., a valuable medicinal plant belongs to the Asparagaceae, is growing in the forests of Hyrcanian ecoregion in northern of Iran. In the present study, molecular authentication of the plant was studied. Four taxa of Ruscus L. along with some species from the genus Danae racemosa and Maianthemum japonicum were selected and the phylogenetic analysis was performed based on cpDNA trn H- psb A spacer. Phytochemical assessment and quantification of two steroid saponins, ruscogenin (RG) and neoruscogenin (NRG) in different plant organs (cladode, stem, rhizome, and root) were also performed by HPLC-PDA analysis. The results of Bayesian analysis revealed that R. hyrcanus and related species R. aculeatus nested in a monophyletic clade as polytomy among the other species of Ruscus and related genus Danae with high statistical support (PP = 1). The HPLC results showed that the highest content (mg/g of dry weight, DW) of RG (1.96) and NRG (0.76) found in the plant rhizome. Cladode, stem, and root of the plant contained 1.15, 0.29, and 0.38 mg/g DW of RG and 0.11, 0.006, and 0.69 mg/g DW of NRG, respectively. These findings can be considered in in situ and ex situ conservation, domestication, breeding, and commercial exploitation programs of this valuable medicinal plant.